"It Is All in the Game!": The Role of Political Skill for Perceived Employability Enhancement. (August 2020) - Chiesa, Rita; Van der Heijden, Beatrice I. J. M.; Mazzetti, Greta; Mariani, Marco G.; Guglielmi, Dina
The current study was aimed at assessing the extent that job-seeking networking may explain the positive association between career planning and self-perceived employability. In addition, the moderator role of political skill in strengthening the relationship between career planning and job-seeking behavior was explored. A sample of N = 2, 561 students and graduates searching for jobs from one of the largest Italian universities filled out an online questionnaire. The hypotheses were tested using structural equation modeling. Results showed that the positive relationship between career planning and self-perceived employability was mediated by job-seeking networking. Furthermore, the association between career planning and job-seeking networking appeared to be stronger for people who possessed greater political skill. This study may advance the comprehension of the added value of proactive career behaviors within the process that links career planning and self-perceived employability. In addition, primary intervention aimed at maximizing graduates' possibilities of attaining employment was suggested.